Traditional Chinese medicine monotherapy in extensive-stage small cell lung cancer - Xinyu Feng; Jianlong Ke; Xiaorong Chen; Xinyue Cao; Jingling Dai; Shaoquan Xiong (Medicine, 2026)
Rationale: Small cell lung cancer (SCLC) is a highly aggressive malignancy. It typically advances quickly, spreads distantly at an early stage, and carries a dismal prognosis, factors that collectively present formidable obstacles to effective treatment. To date, evidence regarding the effectiveness of traditional Chinese medicine (TCM) used alone in extensive-stage SCLC remains sparse. Patient concerns: A 79-year-old man presented with a persistent cough, exertional shortness of breath, hemoptysis with pale-red sticky sputum, and a headache localized to the right forehead, accompanied by difficulty sleeping at night. Diagnoses: Imaging and histopathology confirmed extensive-stage SCLC with right frontal lobe metastasis. Interventions: The patient refused chemotherapy/immunotherapy and received individualized TCM treatment. Outcomes: Serial imaging showed a partial response; symptoms markedly resolved; overall survival reached 15.5 months. Lessons: While findings from a single case must be interpreted cautiously, this experience suggests TCM might contribute to improved outcomes in select patients with extensive-stage SCLC. Further research is needed to clarify its biological mechanisms and define its potential role in clinical practice.